Analisis Peran Orang Tua terhadap Pembentukan Disiplin Siswa Sekolah Dasar - Raisyah Permata Sari; Sartono Sartono (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study aims to analyze the role of parents in shaping the discipline of elementary school students. Discipline is a crucial aspect in supporting academic success and character development from an early age. This research employs a qualitative descriptive approach. The subjects consist of parents, classroom teachers, and the principal at a public elementary school. Data were collected through in-depth interviews, observations, and documentation. The findings indicate that parents play a significant role in fostering discipline through modeling behavior, establishing routines at home, supervision, and effective communication with the school. Supporting factors include active parental involvement and awareness of the importance of character education, while obstacles include parents’ busy schedules and lack of understanding of appropriate parenting styles. This study emphasizes the importance of collaboration between school and family in sustaining students’ disciplined behavior.